HEALTH SCREENING ANALYSIS OF HIGH-RISK PRIMARY SCHOOL STUDENTS OF SK SEKSYEN 7, BANGI - Chua , Yi Jiang; Samsuddin, Syahrizan (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Childhood obesity and metabolic disorders are growing concerns globally. This study examines the health status of primary school children in SK Seksyen 7, Bangi. METHODOLOGY We conducted a cross-sectional study on 116 high-risk primary school students (aged 10 to 12 years old). Anthropometric measurements (weight, height, BMI, waist circumference) and physiological parameters (blood pressure, blood glucose) were recorded. We also performed BMI classification and assessed their metabolic risk. RESULT Among the students, 78% were classified as obese, 13% were overweight, and only 9% had a normal body mass index (BMI). The glycemic results indicated that 97% of the students had normal glucose levels, while 3% were prediabetic. Additionally, only 20% of the students had a normal waist circumference measurement. CONCLUSION The findings highlight the importance of routine health screenings to detect early endocrine disorders in children. Early intervention strategies, including lifestyle modifications, are essential to prevent future metabolic complications.